PWE-057 An analysis of readmission rates and subsequent hospital activity following a non-elective admission in ulcerative colitis (uc) patients. (17th June 2017) - Soubieres, A; Poullis, A; Khoo, J; Ingram, A
Abstract : Introduction: UC is associated with a relative high rate of relapse and is therefore costly 1 . There is evidence to suggest that UC is not always managed optimally and that treatment pathways could be improved with 30 day readmission rates as high as 25% 2 . There have been no UK studies which have examined readmissions rates of UC compared to other benign luminal gastroenterological conditions. Method: NHS Hospital Episodes data (HES) from June 2014 to 2016 were analysed using 3 cohorts. Cohort A: UC patients who have never been on a biologic. Cohort B: General luminal gastroenterology patients excluding IBD patients. Cohort C: UC patients who have received a biologic prior to their first non-elective admission (NEA). All patients must have had at least 1 NEA within the HES data period and hospital activity was extracted following their first NEA. GI cancer and liver disease patients were excluded. Data on numbers of NEAs, Elective admissions, emergency dept.(ED) attendances, Outpatient appts. and Tariff costs were collected and analysed. Results: 1 78 457 patients had ≥1 NEA in the study period amounting to 393, 037 NEAs. The UC Cohorts A and C only contributed 15% of patients and 15% of all Gastroenterology NEAs yet were responsible for 35% of all 30 day readmission costs. ED attendance within 30 days of first NEA was high across all cohorts ranging between 19% to 28% of all patients. Just over 2% of UC patients were on a biologic. The UC cohorts A and C had higher 30 day readmission rates than cohort B, 5.3%, 5.3% and 1.5% respectively. The age distributions of patients with ≥1 NEA was considerably older in Cohort B than the UC cohorts. Cohort C had the youngest profile with patients<40 years accounting for 51% of NEAs compared to 29% for Cohort A and 17% for Cohort B. 30 day readmission rates by region and gender were fairly constant within each cohort. Conclusion: Following a NEA UC patients incur high costs and relatively higher readmission rates compared to the general gastroenterology population despite being a younger population. Readmission rates and post NEA hospital resource do not improve amongst the biologic patients despite biologics being known as a highly effective therapy suggesting that biologics may be being administered too late in the treatment cycle and reserved for the more severe younger patients. High ED attendances across all cohorts suggest that patients do not have necessary access to appropriate IBD and gastroenterology services. References: Poullis A, Soubieres A. The true cost of UC in the UK 24 months following first non–elective admission. Poster presented at BSG Meeting Liverpool 20-23 rd June 2016 Hazratjee Net al, Hospital Readmissions in Patients With Inflammatory Bowel Disease Am J Gastroenterol2013;108:1024–32 Disclosure of Interest: A. Soubieres: None Declared, A. Poullis: None Declared, J. Khoo: None Declared, A. Ingram Conflict with: Andy Ingram is a contractor with Abbvie. AbbVie were the sponsors of this research study. Financial support for this research study was provided by AbbVie. AbbVie participated in the interpretation of data, review and approval of this abstract